Long-term government debt and household portfolio composition - Andreas Tischbirek (Quantitative Economics, 2019)
Formal dynamic analyses of household portfolio choice in the literature focus on holdings of equity and a risk-free asset or bonds of different maturities, neglecting the interdependence of the decisions to invest in equity, short-term and longterm bonds made by households. Data from the Survey of Consumer Finances is used to derive stylized facts about participation in the long-term governmentdebt market and conditional portfolio shares. To explain the mechanisms underlying these facts, I draw on a life-cycle model in which investors have access to three financial assets-equity, long-term debt, and a riskless short-term bond- and are exposed to uninsurable idiosyncratic risk through nonfinancial income as well as aggregate risk through the asset returns. An application shows that the low Treasury returns observed in the US between 2009 and 2013 have quantitatively significant yet transitory effects on the composition of household portfolios. In combination with the observed rise in stock returns, they lead to persistent changes in the participation rate, the conditional portfolio shares, and the distribution of wealth.
Keywords: D10; D15; E21; G11; 330; Dynamic portfolio choice; life cycle; long-term government debt; asset-market participation; survey of consumer finances